Modeling the origin of the ocular pulse and its impact on the optic nerve head - Jin, Yuejiao (2018)
Purpose: To use finite element (FE) analysis to understand the origin of the ocular pulse and predict its biomechanical impact on the optic nerve head (ONH). Methods: An FE model of a healthy eye was reconstructed. The choroid was biphasic and consisted of a solid phase (connective tissues) and a fluid phase (blood). We applied arterial blood pressure at 18 entry sites (posterior ciliary arteries) and venous blood pressure at 4 exit sites (vortex veins). For one cardiac cycle, we reported the resulting pulse volume, the ocular pulse amplitude (OPA), and diastole-to-systole ONH deformations. We also studied the effect of a change in scleral stiffness, in arterial pressure, and in baseline IOP. Results: During the cardiac cycle, a change in arterial pressure resulted in choroidal expansion, which in turn induced a change in IOP (the OPA) and ONH deformations. From diastole to systole, we found that choroidal expansion made the peripapillary retina move anteriorly, but both choroidal expansion and the OPA made the prelamina and LC move posteriorly. The net result was shearing of neural tissues in the neuroretinal rim. Both a stiffer sclera and a higher IOP resulted in a higher OPA, smaller pulse volume, larger diastole-to-systole ONH strains, and neural tissue shear in the neuroretinal rim. Increasing the arterial pressure had the same effect, except that it increased the pulse volume. Conclusions: Our models indicate that, during the cardiac cycle, the OPA and choroidal expansion can deform the ONH with a net shearing of neural tissues within the neuroretinal rim.